Peran Dakwah Islam dalam Pembinaan Karakter Personel Polri Menuju Reformasi Institusional - Wawan Saputra; Agus Darwanto; Miftakhussurur; Mega Satria Nurul Falah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The reform of the Indonesian National Police (Polri) represents an institutional transformation towards higher professionalism and accountability. This study aims to analyze the role of Islamic dakwah (propagation) in fostering the character of Polri personnel as an effort to support institutional reform, particularly in the aspect of cultural change which remains the main challenge for Polri today. The research employs a qualitative method with a descriptive approach through interviews, observation, and documentation at the Mobile Brigade Unit of the South Sumatra Regional Police. Interviews were conducted with 5 Polri members who consistently practice Islamic teachings and 3 civilians. Data analysis utilized the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing with verification through triangulation. The findings reveal that Islamic dakwah plays a strategic role in fostering the character of Polri personnel through enhancing piety, establishing good morals, improving professionalism and integrity, and contributing to cultural reform and increasing public trust. Islamic dakwah within the police environment can be implemented through direct means, written materials, and exemplary conduct. This study recommends integrating Islamic dakwah as a sustainable method of character development for personnel in order to realize a professional, accountable, highly integrous, and humane Polri institution